Cultural and Spiritual Representation in 'Jiwa Jagad Jawi' for Destination Branding - Sophia Novita (UPT Publikasi Ilmiah UNISBA, 2024)
Jiwa Jagad Jawi is a film about spiritual and cultural tourism in Central Java that takes a symbolically rich and meaningful approach. By emphasizing cultural and spiritual symbols, tourism films can enhance perceptions of travel and contribute to the growth of tourist destinations. Previous studies have extensively explored the role of films as tools for destination marketing. This study analyzes how the film constructs a destination image through the prism of Roland Barthes' semiotic theory. Using Barthes' methodology, the film is examined at both the denotative and connotative levels of signification to understand how it portrays the destination as a deeply spiritual and cultural experience. The findings reveal that this short film effectively highlights Yogyakarta's unique blend of rich culture, historical significance, and spiritual depth as key tourist attractions. By skillfully incorporating cultural and spiritual elements, the film introduces the uniqueness of Yogyakarta. It underscores the importance of preserving and celebrating cultural and historical heritage as an integral part of the tourism experience.